Liberalism After Communism The Implications of the 1993 Elections to the Federal Assembly - Szacki, Jerzy (Book collections on Project MUSE., 1995)
In Liberalism after Communism distinguished Polish social scientist Jerzy Szacki discusses the spread of liberalism as the dominant political ideology of Eastern Europe since 1989 and analyses the widespread (but occasionally somewhat beleaguered) belief that the only way forward for the region is through a combination of liberal democracy and free market ideals. He defines liberalism in an East European context - in terms of its historical background, the lack of a liberal tradition in the region and its incompatibility with the communist state. He then goes on to raise the questions of individual autonomy, civil society, economic liberalism and the problems of democratic revolution in East European society, before looking at liberalism's future within the region. The Polish edition was awarded Menzione Speciale by the jury of the Premio Europeo Amalfi, 1994.